Educational psychology - Cline, Tony; Gulliford, Anthea; Birch, Susan (New York : Routledge, 2023)
"Now in its Third Edition, Educational Psychology offers a comprehensive overview of how key advances in social, developmental and cognitive psychology impact upon the role of educational psychologists working today. Written by leading researchers, the book also explores controversies and dilemmas in both research and practice, providing students with a balanced and cutting-edge introduction to both the field and the profession"--
"Second edition published by Routledge 2015" -- Title page verso.
Includes bibliographical references and index.
Keywords: Educational psychology